Le « réalisme magique » de "Prawiek i inne czasy" d’Olga Tokarczuk filtré par la traduction - Elżbieta Skibińska (Ksiegarnia Akademicka Publishing, 2017)
The “Magical Realism” of Prawiek i inne czasy by Olga Tokarczuk Through the Filter of Translation: Comparative Study of the Czech, French and Spanish Translations “Magical realism” in Prawiek i inne czasy has been noticed very quickly by the critics of Olga Tokarczuk’s novel. If some typically Polish elements can be observed in the text’s composition, other “ingredients,” more universal, also appear, but they are “polonised,” if only due to the Polish language of the novel. When comparing an original passage (the chapter Czas Topielca Pluszcza), which contains Slavic mythological elements linked with water, with its translations into Czech, French and Spanish, it appears that “national fantastic” features create differences which enlarge with geographical and cultural distance: the Czech version does not contain many shifts compared with the original, while the French and Spanish versions bring about cultural alterity effects. These, however, should not be considered as an obstacle to the reading.